Youths’ word-of-mouth in a developing country: roles of green promotion and green brand loyalty - Phan, Than Hai; Nguyen, Ngoc Diep; Ha, Hai Giang; Le, Mai Trang; Vu, Phuong Anh; Doan, Hai Anh (Business, Management and Economics Engineering, 2024)
Purpose – This paper investigates the mediating role of green brand loyalty between green brand image and word-of-mouth (WoM) and the moderating role of green promotion and brand social responsibility among Vietnamese youth. Research methodology – Using an online questionnaire from 1st October 2022 to 31st December 2022, 740 valid responses were collected. Findings – The study reveals that green brand loyalty mediates the relationship between brand trust and WoM. Additionally, green promotion significantly moderates the relationship between brand trust and green brand loyalty. The study concludes that green promotion is vital in influencing consumers’ trust in the brand, subsequently increasing their loyalty. Research limitations – This study has not categorized the groups of environmentally friendly products used by young Vietnamese to see if there is a difference. Practical implications – These results provide significant implications for brand managers to enhance the effectiveness of WoM. Originality/Value – Green promotion is an effective strategy for brands to regain consumers’ loyalty and maintain a close relationship between consumers and green brands. Additionally, green brand loyalty emphasizes the significance of green promotion for developing green companies and can serve as a conduit between customers and brands.